How latent patterns of interprofessional working may lead to delays in discharge from hospital of older people living with frailty – 'Patient more confused than usual?'. Issue 3 (8th March 2023) - Redwood, Sabi; Brant, Heather; Maluf, Adriano; Combes, Gill; Neubauer, Kyra; Thomas, Clare; Damery, Sarah; Murigu, Nadine; Hill, Elizabeth; Greenfield, Sheila; Donovan, Jenny L.
Abstract: Unnecessarily delayed discharges from hospital of older people living with frailty can have negative consequences for their health and add significant costs to health services. We report on an ethnographic study at two English hospitals and their respective health and social care systems where we followed 37 patient journeys. The study aim was to understand why delays occur. Our findings indicate that working practices in the study hospitals may have inadvertently contributed to delays. While many pieces of patients' clinical and social information were collected, recorded and accessed in different ways by different professionals, to facilitate a discharge, these pieces needed to be re-found, integrated and re-constructed. A key component of this process was information related to patients' social, family and functional background. This was often missing, not accessed or perceived to be of low value compared to other more readily available clinical information. Patients' re-construction was thus often incomplete, or insufficient to reduce the clinical and prognostic uncertainty associated with frailty and to manage risks inherent in older people's discharge. Where this key component was present and integrated into decision-making in multi-disciplinary team working, uncertainty and risk were managed more constructively and sometimes avoided an escalation of care needs.